Unlimited capacity parallel quantity comparison of multiple integers - Blanc-Goldhammer, Daryn R. (2014)
Research has shown that integer comparison is quick and efficient. This efficiency may be a function of the structure of the integer comparison system. The present study tests whether integers are compared with an unlimited capacity system or a limited capacity system. We tested these models using a visual search task with time delimitation. The data from Experiment 1 and 2 indicate that integers are encoded, identified, and compared within an unlimited capacity system. The data from Experiment 3 indicates that second order magnitude comparisons are processed with a highly efficient limited capacity system.